2019
DOI: 10.1155/2019/6809510
|View full text |Cite
|
Sign up to set email alerts
|

Calculation and Control Methods for Equivalent Resilient Modulus of Subgrade Based on Nonuniform Distribution of Stress

Abstract: The resilient modulus of subgrade is a design parameter of the pavement structure, which is significantly affected by the overlying load and traffic load. It is important to calculate the equivalent resilient modulus of the top surface of subgrade based on the nonuniform distribution of resilient modulus in subgrade. This paper takes the fully weathered granite soil as the research object. Firstly, the soil density of different layers of the subgrade structure is calculated by the degree of compaction of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Ground-penetrating radar (GPR) [22][23][24][25][26] Total station [27][28][29][30][31] InSAR [32][33][34][35][36] Distributed optical fiber [37][38][39][40][41] Subgrade frost heaving Ground-penetrating radar (GPR) [42][43][44][45] Multi-sensor embedding [46][47][48][49][50] Weak subgrade Falling weight deflectometer (FWD) [51][52][53][54][55][56]…”
Section: Subgrade Settlementmentioning
confidence: 99%
See 1 more Smart Citation
“…Ground-penetrating radar (GPR) [22][23][24][25][26] Total station [27][28][29][30][31] InSAR [32][33][34][35][36] Distributed optical fiber [37][38][39][40][41] Subgrade frost heaving Ground-penetrating radar (GPR) [42][43][44][45] Multi-sensor embedding [46][47][48][49][50] Weak subgrade Falling weight deflectometer (FWD) [51][52][53][54][55][56]…”
Section: Subgrade Settlementmentioning
confidence: 99%
“…Experimental results have demonstrated that this method can be effectively used for the accurate detection of weak subgrade distresses. Yao Yongsheng et al [52] put forward the calculation and control method of the equivalent elastic modulus of subgrade top surface under non-uniform stress distribution and carried out the field verification test with a drop weight deflectometer. The results show that the calculation method of the equivalent elastic modulus of subgrade proposed in this study is reasonable and effective.…”
Section: Falling Weight Deflectometermentioning
confidence: 99%
“…Tuan & Chieu: The Effect of Moisture and Fine Grain Content on the Resilient Modulus of Sandy … pressure, lateral pressure, and lateral compression strength [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: B Factors Affecting Resilient Modulusmentioning
confidence: 99%
“…Among the available mechanical response metrics, the most widely used one is deflection [31]. The equivalent resilient modulus is determined using the iterative inverse calculation method according to the principle of deflection equivalence [32,33]. In AASHTO, the current service index of pavement is used as an index to determine the empirical equation for the relative loss coefficient for different subgrade moduli, and the effective resilient modulus of the subgrade is back-calculated based on the average relative loss coefficient [34].…”
Section: Introductionmentioning
confidence: 99%